SYSTEMATIC APPROACH TO IMPROVING OPERATIONAL EFFICIENCY IN MANAGEMENT - A. Goloskokov (Вестник университета)
In the article the process approach to increase of operational efficiency in management is considered. A brief overview of the concepts on this topic from various literature is presented. Factors affecting operational efficiency in the company are considered, and a general method for implementing the task of increasing operational efficiency is presented. The specified method is decomposed into several stages, specific recommendations for their implementation are given and the meaning of each step is described to achieve the task.